Gamificação e Educação Matemática: uma reflexão pela óptica da teoria das situações didáticas - Gomes, Marcelo dos Santos (2017)
This research had the objective of reflecting upon the possible relations between Gamification and the Theory of Didactical Situations. To achieve aforementioned objective, it was developed a bibliographical research that allowed to comprehend and define what gamification is and consequently, the need of studying the links between gaming and math learning and teaching. Even though the gamification theme is becoming bigger in the academic means e in the educational practice, the number of published researches is still little. Hence, a study about gamification and its approaches has been made, and thus, the definition of Karl Kapp has been adopted as it’s believed that his definition better allowed the analysis of gamification as a teaching strategy through the optics of the Theory of Didactical Situations in Mathematics from Guy Brousseau. To help connecting the teaching strategy and theory, researches with focus on teaching and learning of mathematics have been used, which have conducted us to the following observations: the importance and the need to further study gamification, before employing its potentialities, associate gamification and other theories and don’t be limited only to the usage of theories enjoyed by game designers, the importance of more dialogues between teachers and game designers occurring to enrich the use of gamification. Finally, the importance that gamification considers the fundamental role of institutionalization in the learning of a new knowledge, the restructuring of a previously learnt knowledge, or even the improvement of some mathematical skills